Importance of the heart vector origin point definition for an ECG analysis: The Atherosclerosis Risk in Communities (ARIC) study. (January 2019) - Perez-Alday, Erick Andres; Li-Pershing, Yin; Bender, Aron; Hamilton, Christopher; Thomas, Jason A.; Johnson, Kyle; Lee, Tiffany L.; Gonzales, Ryan; Li, Aaron; Newton, Kelley; Tereshchenko, Larisa G.
Abstract: Aim: Our goal was to investigate the effect of a global XYZ median beat construction and the heart vector origin point definition on predictive accuracy of ECG biomarkers of sudden cardiac death (SCD). Methods: Atherosclerosis Risk In Community study participants with analyzable digital ECGs were included (n = 15, 768; 55% female, 73% white, mean age 54.2 ± 5.8 y). We developed an algorithm to automatically detect the heart vector origin point on a median beat. Three different approaches to construct a global XYZ beat and two methods to locate origin point were compared. Global electrical heterogeneity was measured by sum absolute QRST integral (SAI QRST), spatial QRS-T angle, and spatial ventricular gradient (SVG) magnitude, azimuth, and elevation. Adjudicated SCD served as the primary outcome. Results: There was high intra-observer (kappa 0.972) and inter-observer (kappa 0.984) agreement in a heart vector origin definition between an automated algorithm and a human. QRS was wider in a median beat that was constructed using R-peak alignment than in time-coherent beat (88.1 ± 16.7 vs. 83.7 ± 15.9 ms; P < 0.0001), and on a median beat constructed using QRS-onset as a zeroed baseline, vs. isoelectric origin point (86.7 ± 15.9 vs. 83.7 ± 15.9 ms; P < 0.0001). ROC AUC was significantly larger for QRS, QT, peak QRS-T angle, SVG elevation, and SAI QRST if measured on a time-coherent median beat, and for SAI QRST and SVG magnitude if measured on a median beat using isoelectric origin point. Conclusion: Time-coherent global XYZ median beat with physiologically meaningful definition of the heart vector's origin point improved predictive accuracy of SCD biomarkers. Graphical abstract: Highlights: We developed a method to identify the heart vector's origin on vectorcardiogram. Origin of the heart vector corresponds to an isoelectric TP (or TQ) segment on ECG. Time-coherent global XYZ beat properly describes electrophysiology. Proper beat improves the predictive accuracy of sudden cardiac death biomarkers.